Transformation from Livestock Barter to Cash Payments in Manggarai Paca Bridewealth Traditions - Yolinda Yanti Sonbay; Beatrix Yunarti Manehat; Philipus Tule (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Paca, the bridewealth practice in the Manggarai community, has shifted from barter-based payments such as livestock, land, and jewelry to predominantly cash transactions. This transformation, known as Kaba Agu Jarang Satu Cikang, reflects wider socio-economic changes and raises questions about its cultural and symbolic implications within the marriage market. This study analyzes paca as a transactional mechanism, explores its transition to cash payments and the resulting shifts in symbolic meaning, and interprets paca as a form of social accounting amid modernization. Using transcendental phenomenology, data were collected through focus group discussions, interviews, and documentation to capture lived experiences from multiple perspectives. The findings show that paca increasingly resembles business transactions and corresponds with accounting concepts reflected in PSAK 55, PSAK 23, and PSAK 58, indicating a movement from sacred ritual toward a more commercialized process. Despite this shift, paca continues to function as social accounting by mediating relationships and maintaining cultural cohesion. This study contributes to understanding how customary practices adapt to economic change and offers practical insight for community stakeholders to balance modernization with the preservation of cultural and symbolic values.